Thrombotic microangiopathy induced by interferon beta in patients with multiple sclerosis: three cases treated with eculizumab - Allinovi, Marco (Clin Kidney J, 2017)
BACKGROUND: Interferon-beta (IFN-beta) is one of the most widely prescribed medications for relapsing-remitting multiple sclerosis (RRMS). IFN-related thrombotic microangiopathy (TMA) is a rare but severe complication, with a fulminant clinical onset and a possibly life-threatening outcome that may occur years after a well-tolerated treatment with IFN. Most patients evolve rapidly to advanced chronic kidney disease and eventually to renal failure. METHODS: We performed a retrospective analysis of TMA cases diagnosed and managed in our Nephrology Department from 2010 to 2015, and performed a literature review of IFN-beta-induced TMA. RESULTS: Three cases of TMA among patients treated with IFN-beta were identified who did not show any renal improvement following conventional therapy: IFN withdrawal and plasma exchange (PE, range 8–18) sessions. All of them responded favourably to eculizumab, with progressive clinical and renal improvement, allowing dialysis discontinuation, without recurrence of TMA during a long-term follow-up (range 1–5 years). CONCLUSIONS: TMA is a recognized severe complication in RRMS patients treated with IFN-beta. Withdrawal of IFN and treatment with PE, steroids or rituximab did not improve the poor renal prognosis in our three patients and in all the previously described cases in the literature. In our experience, eculizumab had a strikingly favourable effect on renal recovery, suggesting a role of IFN-beta as a trigger in complement-mediated TMA. Neurologists and nephrologists should be vigilant to this complication to prevent possibly irreversible renal damage.